Rapid restoration of normoglycaemia using intravenous insulin boluses. - Dunnett, J; Steemson, J; Sear, J; Turner, R; Holman, R (1990)
The reduction of elevated fasting plasma glucose levels to near normal by repeated intravenous bolus insulin doses, given according to a simple algorithm, has been studied in 17 Type I and 23 Type II, healthy diabetic patients. Using a formula based on the patient's plasma glucose, height and bodyweight with insulin boluses given every 30 min if the plasma glucose remained above 6 mmol/1, plasma glucose levels were reduced to less than 7.5 mmol/1 in 28 (70%) patients by 60 min at which time the mean (+/- 1 SD) plasma glucose level in the Type I diabetic patients had reduced from 18.2 +/- 4.9 to 8.9 +/- 3.5 mmol/1 and in the Type II diabetic patients from 12.3 +/- 3.1 to 5.9 +/- 1.4 mmol/1. None of the patients had symptomatic hypoglycaemia although in one Type I patient the plasma glucose level fell to 2.2 mmol/1. The rate of fall of glucose in the less insulin sensitive patients was not increased by giving more insulin. The regimen allows a reproducible and prompt glycaemic reduction in fasting diabetic patients.